Extension of SUSY SU(5) GUTs with Nelson-Barr models - Junji Hisano; Moe Kuroda (Journal of High Energy Physics)
Abstract In this paper we extend the supersymmetric SU(5) GUTs with the Nelson-Barr (NB) models. The NB models are a candidate for the solution of the strong CP problem. We show that the parameters in the CKM matrix are reproduced while the mass ratios of the down-type quarks and leptons in the second and third generations are explained in the minimal extension.